PENGARUH KOMITMEN ORGANISASIONAL DAN PROFESIONAL TERHADAP KEPUASAN KERJA AUDITOR: MOTIVASI SEBAGAI VARIABEL INTERVENING - Nurita Fauzia (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to find out 1) organizational commitment influences motivation 2) professional  commitment  influences  motivation,  3) organizational  commitment influences job satisfaction 4) professional commitment influences job satisfaction5) motivation influences job satisfaction and 6) organizational commitment and commitment  professionals  influence job  satisfaction  through motivation as  an intervening variable. The method used in this study is the method of data analysis using descriptive analysis with a quantitative approach. The population in this study were auditors who worked at the Public Accountant Firm in Malang City and Surabaya, where the number of Public Accountant Firm in Malang was 12 and Surabaya as many as 44 to total Public Accountant Firm of 56 (Source: directory IAI (Ikatan Akuntansi Indonesia, 2017) In the research sampling process researchers distributed questionnaires to auditors in Malang City and Surabaya with a total sample of 125 respondents. The data analysis technique used path analysis. The results of this study indicate that there is an influence of organizational commitment to motivation, professional commitment influences motivation, organizational commitment influences job satisfaction, professional commitment influences job satisfaction, motivation influences job satisfaction and organizational commitment and professional commitment influences job satisfaction through motivation as an intervening variable. sis in this study proved to be accepted.Keywords: Commitment, Auditor Job Satisfaction and Motivation